Application of the Stake Evaluation Model to evaluate Kurikulum Merdeka in creating student well-being - Risti Dwi Lestari (Inovasi Kurikulum, 2023)
The demographic bonus has become unavoidable for Indonesia in 2030–2045. Will this condition be advantageous or disadvantageous depending on how HR is currently managed? The scope of HR management in this study is in the field of education, and the main actor is the government. Bearing in mind that in accordance with the mandate of the 1945 Constitution of the Republic of Indonesia Article 31 (1) and its Amendment Chapter XIII concerning education and culture, obliges the government to be responsible for educating the life of the nation and creating general welfare? This study aims to determine the appropriate evaluation model to assess the implemented curriculum with regard to the welfare of students through the characteristics of a "humanistic approach". The research method used is descriptive-qualitative through a literature study with a review of books, articles, journals, and other relevant sources of information. This literature found that stakeholder evaluation is suitable for evaluating the implementation of the Independent Curriculum, considering that this model compares implementation in the field with official standards or references in implementing a program through two components, namely description, and assessment. These two things were broken down into the three main components of the first educational program: antecedents (inputs), transactions (processes), and outcomes (results). However, empirical results are still needed to support this research, such as case studies, which are intended to get more concrete results. AbstrakBonus demografi sudah menjadi hal yang tidak dapat dihindari Indonesia pada tahun 2030-2045. Akankah kondisi tersebut menjadi kelebihan / kerugian tergantung dari bagaimana saat ini mengelola SDM itu sendiri. Cakupan dalam pengelolaan SDM pada penelitian ini yaitu di bidang pendidikan dan aktor utamanya adalah pemerintah. Mengingat sesuai dengan amanat UUD Republik Indonesia Tahun 1945 Pasal 31 (1) dan Perubahannya bab XIII tentang pendidikan dan kebudayaan. Di mana mewajibkan pemerintah bertanggung jawab dalam mencerdaskan kehidupan bangsa dan menciptakan kesejahteraan umum. Kajian ini bertujuan untuk mengetahui model evaluasi yang tepat untuk menilai kurikulum yang diimplementasikan dengan kesejahteraan siswa melalui karakteristik “pendekatan humanistic”. Metode penelitian yang digunakan adalah deskriptif kualitatif melalui studi kepustakaan dengan telaah buku, artikel, jurnal, dan sumber informasi lainnya yang relevan. Dari studi literatur ini ditemukan bahwa evaluasi stake cocok digunakan untuk mengevaluasi implementasi Kurikulum Merdeka mengingat model ini membandingkan antara pelaksanaan di lapangan dengan standar atau acuan yang resmi dalam melakukan sebuah program melalui dua komponen yaitu deskripsi dan penilaian. Kedua hal tersebut, diturunkan kembali menjadi tiga komponen utama program pendidikan pertama, antecedent (masukan), transaction (proses), dan outcomes (hasil). Namun, masih dibutuhkan hasil empiris untuk mendukung penelitian ini, seperti studi kasus yang dimaksudkan agar mendapatkan hasil yang lebih konkrit.Kata Kunci: Evaluasi kurikulum; Kurikulum Merdeka; Model Evaluasi Stake